Pengaruh Current Ratio dan Quick Ratio Terhadap Return On Asset: (Studi Kasus Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Delvi Rahma Novianti; Juhaini Alie; Endah Dewi Purnamasari (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to analyze the effects of current ratio (CR) and quick ratio (QR) on return on assets (ROA) in the food and beverage sub-sector listed on the Indonesia Stock Exchange. Financial report data were collected through documentation, literature study, and observation. This study implemented multiple linear regression methods to analyze data. The results of the investigation prove that partially CR has a significant effect on ROA. On the other hand, QR has no significant effect on ROA. Simultaneously, CR and QR have a significant effect on ROA. This research offers empirical evidence on the discussion of CR, QR, and ROA especially for the food and beverage industry.